Objective measurement of egg yolk colour - Konrád, Szilárd; Kovács, Anett; Kovácsné Gaál, Katalin (Animal welfare, Ethology and Housing Systems (AWETH), 2012)
The aim of this study was to comparison the measurements of Hungarian yellow hen’s eggs and commercial eggs yolk colour with DSM Roche Yolk Colour Fan and HunterLab Miniscan XE Plus spectrophotometer. It was examined 131 Hungarian yellow hen eggs and 28 commercial eggs. The yolk colour of commercial eggs was more intensive and reddish. The results of the measurements with DSM Roche Yolk Colour Fan and spectrophotometer showed this difference. By the Hungarian Yellow hen’s yolk colour was 8,36 with the DSM Roche Yolk Colour Fan, the lightness value (L*) was 62,24, the redness value (a*) was 13,77 and the yellowness value (b*) was 60,46. By the commercial eggs it was measured 14,67 with the DSM Roche Yolk Colour Fan, the lightness value (L*) was 51,67, the redness value (a*) was 30,44 and the yellowness value (b*) was 53,36. The correlation rate between lightness value (L*) and DSM Roche Yolk Colour Fan was strong (r = -0,9198). The correlation rate between redness value (a*) and DSM Roche Yolk Colour Fan was also strong (r = 0,9618), but the correlation rate between yellowness value (b*) and DSM Roche Yolk Colour Fan was weak (r = 0,3763).